Synthesis of Nanopartical-based Binary Oxide Electrode TiO2-ZrO2 with Carrot-derived Natural Dye Extract for Dye Sensitized Solar Cell (DSSC) Application - Win, S.; Win, T.; Maung, Y.; Soe, K.; Kyaw, T.; Tan, C.; Sokkalingam, Rajalingam; Oo, Z. (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2015)
Dye-sensitized solar cell (DSSC) is the third generation of thin film solar cell. In this work, carrot fruit dye was prepared and used in DSSC as a sensitizer. TiO2 –ZrO2 fine binary oxide was mechanochemically prepared and made paste. TiO2 –ZrO2 paste (colloidal) was deposited onto FTO/glass in two ways, i.e. as single and double coatings by rolling method. It was immersed in the carrot solution to get dyed cell. The dyed TiO2 -ZrO2 -FTO/glass cell was offset with the FTO/glass cell coated with adhesive carbon paste. Photovoltaic properties of prepared TiO2 –ZrO2 DSSC cell were measured. Results showed that the efficiency of double coating cell was greater than that of the single coating cell. According to the fill factor from the experiments, both the DSSC cells were acceptable for industrial requirement. Hence, it can be concluded that the results obtained were acceptable in the use of cost-effective and eco-favourable dye-sensitized solar cell.